Tracking Changes in Neuropathic Pain After Acute Spinal Cord Injury - Scheuren, Paulina Simonne; Gagné, Martin; Jutzeler, Catherine Ruth; Rosner, Jan; Mercier, Catherine; Kramer, John Lawrence Kipling (Frontiers in Neurology, 2019)
Neuropathic pain represents a primary detrimental outcome of spinal cord injury. A major challenge facing effective management is a lack of surrogate measures to examine the physiology and anatomy of neuropathic pain. To this end, we investigated the relationship between psychophysical responses to tonic heat stimulation and neuropathic pain rating after traumatic spinal cord injury. Subjects provided a continuous rating to two minutes of tonic heat at admission to rehabilitation and again at discharge. Adaptation, temporal summation of pain, and modulation profile (i.e., the relationship between adaptation and temporal summation of pain) were extracted from tonic heat curves for each subject. There was no association between any of the tonic heat outcomes and neuropathic pain severity at admission. The degree of adaptation, the degree of temporal summation of pain, and the modulation profile did not change significantly from admission to discharge. However, changes in modulation profiles between admission and discharge were significantly correlated with changes in neuropathic pain symptoms (p=0.027; R2=0.323). The modulation profile may represent an effective measure to track changes in neuropathic pain severity from early to later stages of spinal cord injury.